(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: In the mid-20th century (the 1950s), public health was badly threatened by a deadly virus known as poliovirus. Poliomyelitis is a highly contagious, fatal, and exclusive human disease caused by the poliovirus that affects mostly children under the age of five. Among the disabilities, a low level of physical activity is determined in polio survivors, which indicates the need for assistance in mobility. Aim of the study: The study aimed to determine the correlation between family support and self-efficacy among paralytic polio survivors. Methodology: An analytical cross-sectional study was conducted using the Correlational study design to determine the association between family support and self-efficacy. A total of 152 participants were included in the study from the paraplegic center Hayatabad Peshawar KPK through consecutive sampling techniques. Data was collected through a validated and translated questionnaire. Data were analyzed using SPSS version 22. Pearson correlation, independent sample T-test, and Chi-square tests were applied to determine the correlation and association among variables. Results: The study findings resulted that among 152 participants, 97 were male and 57 were female. The mean age of the current study participants was 32.54 ± 8.030 years. There was a highly significant correlation with the P-value of 0.001 between family support and self-efficacy among paralytic polio survivors. Some demographic variables like gender, Education, paralyzed parts of the body, and age of onset of disease presented highly significant positive associations. Conclusion: The correlation between family support and self-efficacy was highly significant. Participants who had more family support had high self-efficacy. Furthermore, the study findings suggested that the hospital management should arrange workshops, seminars, and other educational programs for polio survivors and their family members to educate them to increase family support for the paralytic polio survivors.